IR-Supported Thermogravimetric Analysis of Water in Hydrogels - Enev, Vojtěch; Sedláček, Petr; Řihák, Marek; Kalina, Michal; Pekař, Miloslav (Frontiers in Materials, 2022)
Isothermal thermogravimetry in a kinetic mode and time resolved infrared spectroscopy were used to characterize water and its binding in hydrogels formed by interactions between hyaluronan and micelles of Septonex, an oppositely charged surfactant. Thermogravimetry provided a detailed insight into the dehydration kinetics of the gel and thus to bring indirect information on the strength of the water binding in the hydrogel network. Infrared (IR) spectroscopy complemented the study with direct analysis of structural changes occurring in the gel during its dehydration. IR spectroscopy thus contributed to understanding the processes which were observed in thermogravimetry, qualitatively, on the molecular level. This study could contribute to a broader application of the combined thermogravimetry -IR approach in study of hydrogel materials and development of their applications, especially in bio-related areas where water is among key players.